The Effect of Transformational Leadership, Organizational Structure and Learning Culture on School Innovation Capacity - Asbari, Masduki (AGUSPATI RESEARCH INSTITUTA, 2024)
This research aims to measure the influence of transformational leadership, learning culture and organizational structure on school innovation capacity. Data collection was carried out using simple random sampling via electronics on a population of private school teachers in Indonesia. The results of the questionnaire that were returned and valid were 800 respondents as a sample. Data processing uses the SEM method with SmartPLS 3.0 software. The results of this research are that transformational leadership, learning culture and school organizational structure have a positive and significant effect on school innovation capacity. Transformational leadership has a positive and significant effect on learning culture and school organizational structure. The novelty of this research is to propose a model for building school innovation capacity through transformational leadership from a learning organization perspective. This research can pave the way to increase the readiness of the world of education in Indonesia, especially private schools, to face the industrial revolution 4.0.